Ultrasound evaluation of focal neuropathies in athletes: a clinically-focused review. Issue 3 (6th January 2015) - Peck, Evan; Strakowski, Jeffrey A
Abstract : Focal neuropathies represent a rare but clinically important and potentially challenging aetiology of pain in athletes. Diagnostic ultrasound is commonly used in the evaluation of nerve entrapments, and has several advantages over other imaging modalities, including high resolution, portability, lack of ionising radiation, low cost, point-of-care access, ease of contralateral comparison and capability of Doppler and dynamic imaging techniques. In this review, we discuss the use of ultrasound for the evaluation of injuries to the brachial plexus including 'stingers, ' suprascapular nerve, ulnar nerve, radial nerve, common fibular nerve, tibial nerve and interdigital nerves of the foot at selected common sites of entrapment.